Cost-effective one-time configuration for bridge-linked thermoelectric generator array using INFO optimizer - Yousri, Dalia; V., Sukanya; Farag, Hany E.Z.; B., Bijukumar; El-Saadany, Ehab (Journal of cleaner production, 2024)
One of the key mechanisms of enhancing the power output of Thermoelectric Generators (TEG) under nonuniform temperature distribution (NUTD) is to restructure their arrays to disperse the NUTD profiles. Existing research works in this area primarily propose dynamic reconfiguration techniques of TEG arrays as a potential solution to maximize their output powers while taking no notice of the highly associated costs of their implementation, i.e., sensors, switches, and maintenance, in addition to the complexity of operation and limited service lifetime of switches. To alleviate these drawbacks, this paper introduces an optimization model for a one-time configuration (OTC) of TEG arrays to maximize their output powers while accommodating multiple NUTD profiles simultaneously. Using the INFO optimizer, the introduced optimization model yields the OTC layout for both symmetrical and asymmetrical TEG arrays across various NUTD scenarios. Given its superior performance, the optimization model is applied to the bridge-linked (BL) TEG array and compared to other configurations such as series (S), series-parallel (SP), and standard BL. The results of the proposed OTC model are compared with (1) standard, non-optimized SP and BL configurations and (2) different dynamic-based reconfiguration techniques. Further, the performance of the proposed model is tested and validated experimentally in the laboratory for the available symmetrical hardware setup, 5 × 5, TEG array under varying NUTD profiles. Compared to dynamic reconfigurations, the results show that the proposed OTC technique provides a partially optimal and cost-effective solution to enhance the output power of TEG arrays under different NUTD. Specifically, for 9×9 and 10×15 TEG arrays, the OTC saves approximately 1,498.5 ($) and 2750 ($) compared to dynamic reconfigurations, respectively. Moreover, BL-based OTC enhances the TEG array harvested power by maximum values of 1.7532%, 2.43%, and 3.156% compared with the standard S, SP, and BL configurations, respectively, based on the hardware setup. Throughout the detailed comparison between the proposed OTC and dynamic reconfiguration techniques, this paper contributes to a deeper understanding of the trade-offs between these configuration techniques and addresses a critical gap in the current research landscape of enhancing the output powers of TEG arrays. •Introducing a cost-effective static configuration as a one-time solution.•Presenting a robust optimizer for seamless dynamic reconfiguration.•Comparing one-time versus dynamic config, balancing power, cost, and complexity.•One-time setup boosts harvested power, providing significant cost savings.•Dynamic configuration amplifies TEG array power but with added cost and complexity.